2021
DOI: 10.3390/nu13114156
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Exploration of Obesity-Related Eating Behaviour Patterns in a Sample of Saudi Preschoolers Aged 2–6 Years through the Children’s Eating Behaviour Questionnaire

Abstract: Background: The Children’s Eating Behaviour Questionnaire (CEBQ) is used with parents to determine the characteristics of eating behaviour of their children and, consequently, children’s propensity to become obese. It has been successfully used mainly in Western countries, but not in Saudi Arabia. In this pilot study, we explored the use of the Saudi version of the CEBQ for preschool children aged 2–6 years in Saudi Arabia, and assessed the associations between eating behaviours and children’s age, gender and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Children in the overweight/obesity group had the lowest scores of these subscales in comparison to the other two groups. Similar to the findings of this study, both these subscales have been reported to be strongly associated with childhood obesity in previous studies (10)(11)(12)(13)26). Therefore, we can assume that eating behaviours represented by these two subscales highly correlate with childhood obesity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Children in the overweight/obesity group had the lowest scores of these subscales in comparison to the other two groups. Similar to the findings of this study, both these subscales have been reported to be strongly associated with childhood obesity in previous studies (10)(11)(12)(13)26). Therefore, we can assume that eating behaviours represented by these two subscales highly correlate with childhood obesity.…”
Section: Discussionsupporting
confidence: 91%
“…Overweight/obese children had higher scores on this subscale compared to other groups, and it can be considered that this subscale highly correlates with childhood obesity. Similar results have been obtained in studies in Netherlands (10), Chile (13), Canada (11), Portugal (12), and Saudi (26). Therefore, paediatricians need to monitor children for similar eating behaviours so that they can identify children who are at risk of being overweight or obese at the earliest.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, 63.2% belonged to middle social class. Likewise, Silva et al [28] in Brazil and Al-Hamad et al [29] in Saudi Arabia declared that younger children had higher scores in the subscale satiety responsiveness.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, not every observed difference between mean scores in given subscales was confirmed in the regression analysis, thus further studies are needed. Finally, admittedly, the original structure of the CEBQ was confirmed in a study that involved older children [ 34 ]; however, this questionnaire has also previously been used among younger children [ 20 , 30 , 39 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…CEBQ is a psychometric tool for assessing eating behaviors in children and was originally developed and validated by Wardle et al [ 34 ]. Since then, CEBQ in original or modified versions has been used in multiple studies, involving wide age ranges of study subjects (from 12 months [ 35 ] up to 16 years old [ 20 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]). Originally, the CEBQ included eight subscales, four of them representing “food approach” traits—food responsiveness (FR), enjoyment of food (EF), emotional overeating (EOE), and desire to drink (DD), with the remaining four representing “food avoidance” eating traits—satiety responsiveness (SR), food fussiness (FF), slowness in eating (SE) and emotional undereating (EUE) [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%